PENGARUH KEPEMIMPINAN, DISIPLIN, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KESEHATAN KABUPATEN KAMPAR - Supardi Supardi (Jurnal Riset Manajemen Indonesia, 2020)
Research to determine the effect of leadership, discipline, competence and compensation on the performance of employees in the Dinas Kesehatan Office Kampar Regency. Sampling was carried out by 104 census employees. Data analysis carried out by multiple linear regression models. Based on the simulthan test results, the variable of leadership, discipline, competence and compensation have a significant effect on the performance of employees in the Dinas Kesehatan Office Kampar Regency. Based on the partial test results, the variable of leadership, discipline and compensation have a significant while the competency variable doesn’t significantly on the performance of employees in the Dinas Kesehatan Office Kampar Regency. Contribution of independent variables to the dependent variables is equual to 70% while the remaining 30% is influenced by other variables not examined in this study.